Analysis for policy : the complicated problem of abortion regulations in Indonesia - Maulida, Uci Putri (BKM Public Health and Community Medicine, 2021)
Objective This paper reviewed analysis for policy the Government Regulations Republic of Indonesia No. 61 of 2014 concerning Reproductive Health that also received a lot of comments because the discussion regarding the purpose of "abortion" was still inadequate. Content Reproductive health problems in adolescence are one of the main focuses in Reproductive Health. According to the ARH report (2017), it is estimated that 19% of adolescents in developing countries have experienced pregnancy. Girls under 15 years even contributed about 2 million of the 7.3 million births in adolescents under 18. In 2014, an estimated 3 million adolescents aged 15-19 years had unsafe abortions. In a study conducted by Utomo in 2011, it was stated that 32% of sexually active adolescents end up in deliberate abortion (Diarsvitri et al in the ARH Report, 2017). The incidence of criminal provocative abortion itself, in Indonesia reaches 2.5 million cases per year, or 43 abortions for every 100 pregnancies, and 30% of them are performed on people aged 15-24 years (Nugroho et al. 2018). Abortion itself contributes to the high incidence of MMR in Indonesia and in other countries, especially in the incidence of unsafe abortion. According to WHO, about 10-50% of deaths are caused by abortion. The policy regarding the issue of abortion has been discussed in the Government Regulations Republic of Indonesia No. 61 of 2014 concerning Reproductive Health, which in its contents also discusses the purpose of medical emergencies. As the policy progressed, this regulation also received a lot of comments. Conclusion Evaluation criteria are more effective in preventive efforts to prevent abortion, namely by preventing unwanted pregnancies through strengthening regulations related to reproductive health and reproductive health education programs since adolescence in all lines.